British trade unionism : select documents - Robertson, N.; Sams, K. I. (Oxford : Basil Blackwell, 1972)
What Robertson and Sams have put together is not a "reader" of articles and essays of the type often used in courses as a supplement to or a substitute for a textbook, but chiefly a collection of primary documents. For their model they have taken W. Milne-Bailey's Trade Union Documents (1929). Like Milne-Bailey, they introduce their collection with a brief essay on the history of industrial relations during the period of coverage: 1914-69. They also introduce each of the main sections of documents, including the appendix on "Developments in 1970," with a concise commentary.
rpm 26/03/2018
Loans
Keywords: Labor unions; Industrial relations